``Pak SUSNO cerdas banget'' Compliment as a Realization of Brown and Levinson's Politeness Strategy in Netizen Responses on YouTube - Pramujiono, Agung; Ardhianti, Mimas; Widya Hanindita, Amelia; Dian Andanty , Ferra (KnE Social Sciences, 2024)
In interacting, speakers will try to build harmony with their speech partners so that their speech is polite and not face threatening. Likewise with netizens when responding to uploads on YouTube. Even though based on surveys by Microsoft, Indonesian netizens are said to be uncivilized, but there are many netizens who maintain politeness in interacting. One strategy used is to compliment. This phenomenon is interesting to describe through research. The research aimed to describe and explain the use of compliments as a realization of the Brown and Levinson netizen’s politeness strategy in responding to uploads on YouTube. This research was a descriptive qualitative research using a cyberpragmatic perspective. The research data were utterances that realized Brown and Levinson’s compliment strategy. Research data sources: (1) Pidato pertama Moeldoko usai terpilih sebagai ketum Demokrasi versi KLB Deli Serdang (https://www.youtube.com/watch?v=sH_LeUYEktk), (2) SBY soal KLB Moeldoko (https://www.youtube.com/watch?v=zAtIiAnUxEU), (3) ILC-Suhu politik semakin memanas (https://www.youtube.com/watch?v=kDUwkJJSCA4), dan (4) ILC-Di balik polisi tembak polisi (https://www.youtube.com/watch?v=_4bjW51ef3Y). The data were taken by the documentation method using the technique of “simak bebas libat cakap (SBLC)”. Furthermore, the data were analyzed using descriptive techniques following the stages of the interactive model. Based on the results of data analysis, it can be found that the realization of compliments as a politeness strategy includes (1) compliment for attitude, (2) compliment for character, (3) compliment for behavior, (4) compliment for speech, (5) compliment for intelligence, (6) compliment for academic achievement, and (7) compliment for work performance. The results of this research strengthens the politeness theory of Brown and Levinson, enriches the study of cyber pragmatics, and can also be implemented in learning, especially in building the character of students. Keywords: compliment, netizen response, politeness strategies, youtube